COMPARATIVE ESTIMATION OF THE STATE OF THE CAPILLARY NETWORK OF THE MUCOUS MEMBRANE OF UNDERDENTURE SPACE AND SPEED OF THE ATROPHY OF ALVEOLAR PROCESS WITH PROSTHETICS MADE FROM DIFFERENT MATERIALS - V.G. Shuturminskiy (Ukrainian Medical Stomatological Academy, 2015)
Purpose: to estimate the state of hard and soft tissues of underdenture area in patients during the application of dentures from the contemporary basic materials. Methods: the clinical experiments were conducted before 5 groups - in 316 patients, by which were made the partial plate prostheses. The durability of capillaries was investigated with the aid of the electron- vacuum apparatus on the upper and lower jaws throughout the beginning of prosthetics and after the fixation of dental prostheses through 1 weeks, 1 month, 1 year. Studies of the speed of the atrophy of alveolar processes were studied employing the procedure of Ivannikov (Ukraine) in the our modification. The study of models was produced before the apparatus for measuring the models, which operating unit - inductive measuring device with the numerical indication. Results: the data of resistance in patients in Group 1 for 2 years had a very slight tendency to decrease: (42,30 ± 0,97); (40,00 ± 0,81); (42,8 ± 0,74), respectively, indicating a profound violation of the vascular area prosthetic bed. Indicators capillary resistance in the 2nd group of patients studied for 6 months. Slightly increased from (26,30 ± 0,49) to (38,00 ± 0,09), and at 1 and 2 years almost returned to normal - (47,50 ± 0,05); (55,00 ± 0,77). Investigating resistance of capillaries in the third group, we have indicators that show an increase in digital indicators period: 1, 6 months, 1 and 2 years, although the norm indicators have not returned even after 2 years: (44,30 ± 0, 31); (53,80 ± 0,40); (53,00 ± 1,35); (51,50 ± 1,01), respectively. Similar changes numerical values in the same period were also observed in the 4th group: (45,10 ± 0,87); (54,40 ± 1,05); (53,90 ± 0,89); (51,85 ± 1,08), respectively. On the 14th day after the imposition of the prosthesis height of the crest of the alveolar bone begins to decrease, but the extent of its reduction in the various study groups varies. In comparison with the data obtained in patients in Group 1, the resorption of the alveolar crest was respectively 28, 34 and 45% less in patients 2, 3 and 4th groups. The results of the measurement models of the jaws of 1 year virtually reflect trends, highlighting the results of determining the height of the crest of the alveolar bone on the 30th day. This result indicates that after 30 days. height of the crest of the alveolar process does not change, i.e.  by this time, apparently ends of bone remodeling in extraction sites. However, the lowest degree of atrophy obvious prosthetic bed 5 minutes patients. Our studies have shown that patients with acrylic prosthesis (group 1), the flow rate of atrophy in the period up to 1 year -2.45 mm in patients with prostheses made of polypropylene (Group 2) -2.25 mm, which is 9.6% higher than the results of the 1st group. When analyzing the results obtained from the use of nylon prosthesis (group 3) and prostheses made of PP copolymer "Tripplene R 359" (group 4) 1 year after the study, the results were slightly higher (- 1,580 ± 0,102 and -0,870 ± 0.039, respectively), which was 35.5 and 70.8% compared with the level of atrophy caused by acrylic dentures. As for the patients of Group 5, with dentures made on our technology, treated in a glow discharge plasma, the level of atrophy was 3 months. 0.65 mm, and after 1 year - 0.88 mm, which is only 35.9% of the level of atrophy of acrylic dentures. Conclusions: the conducted investigations showed that the prostheses from the copolymer "Tripplene R 359" due to the optimum elasticity and the absence of laminar edge maximally preserve the vascular network of the mucous membrane of the cavity of mouth, is reduced the speed of the atrophy of alveolar processes practically to the control indices; and they decrease a quantity of development of traumatic prothetic stomatites.